Study On Mechanical Properties Of Node And Internode From Different Parts Of Gigantochloa Ligulata Bamboo - Devarajan, Devandran (Universiti Sains Malaysia, 2021)
With exponential worldwide population increase and accompanying environmentally damaging consumption of natural resources, alternative and sustainable materials are being researched to meet human demands. Bamboo's features, such as its rapid growth, renewable nature, and ease of availability as raw material, satisfy the human demand for environmentally friendly building materials. Bamboo is one of the fastest-growing plants on the planet, with numerous species varying in size. Even though bamboo has been used as a construction material for thousands of years, there has been little research on the mechanical properties of bamboo itself. Bamboo's use in construction has long been overlooked due to a lack of understanding about its properties. As a consequence, this study presents an investigation of the mechanical properties of nodes and internodes from various height positions (top, middle, and bottom) of a bamboo species found in Malaysia. In this study, the mechanical properties of the Gigantochloa Ligulata bamboo species are determined (compression, shear, and tensile). ISO 22157 was used as a reference to test the mechanical properties of bamboo culms at various heights. Based on the test results, the compressions and shear strengths of internodes outperform those of nodes. From the bottom to the top of the bamboo culm, the nodal section for compression and shear exhibits an increasing tendency. All the mechanical properties show an increasing trend from bottom to top of the bamboo culm.